An introduction to criminal psychology - Durrant, Russil (Routledge, Taylor & Francis Group, 2018)
Understanding criminal behaviour : an overview -- Juvenile delinquency and developmental theories of crime -- Mental disorder and crime -- Aggression and violence -- Violent offending -- Sexual offending -- Collective violence -- Drugs and crime -- Property offending -- White collar, corporate and environmental crime -- Crime prevention -- Criminal justice responses to crime -- The rehabilitation and reintegration of offenders -- Bibliography -- Index